2020
DOI: 10.3390/geosciences10070276
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Ensemble Kalman-Based Methods for Estimating Aquifer Parameters from Virtual 2-D Hydraulic and Tracer Tomographic Tests

Abstract: We compare two ensemble Kalman-based methods to estimate the hydraulic conductivity field of an aquifer from data of hydraulic and tracer tomographic experiments: (i) the Ensemble Kalman Filter (EnKF) and (ii) the Kalman Ensemble Generator (KEG). We generated synthetic drawdown and tracer data by simulating two pumping tests, each followed by a tracer test. Parameter updating with the EnKF is performed using the full transient signal. For hydraulic data, we use the standard update scheme of the EnKF with dampi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 107 publications
(140 reference statements)
1
12
0
Order By: Relevance
“…We applied the same ensemble-Kalman filter based methods for parameter estimation as those used in the synthetic study of the companion paper [58]: the Ensemble Kalman Filter (EnKF) and the Kalman Ensemble Generator (KEG). Ensemble-Kalman filter based methods are recursive processes with a forecast-update cycle defined by Equation (13) (forecast) and Equation (14) (update) [71].…”
Section: Parameter Estimation With Ensemble-kalman Based Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We applied the same ensemble-Kalman filter based methods for parameter estimation as those used in the synthetic study of the companion paper [58]: the Ensemble Kalman Filter (EnKF) and the Kalman Ensemble Generator (KEG). Ensemble-Kalman filter based methods are recursive processes with a forecast-update cycle defined by Equation (13) (forecast) and Equation (14) (update) [71].…”
Section: Parameter Estimation With Ensemble-kalman Based Methodsmentioning
confidence: 99%
“…This work is the follow up to a synthetic study [58] on the application of two data assimilation methods to the estimation of spatially distributed hydraulic conductivity: (1) the Ensemble Kalman Filter (EnKF) and (2) the Kalman Ensemble Generator (KEG). In the preceding synthetic study [58], we showed that the EnKF and KEG are well-fitted for the estimation of spatially distributed hydraulic conductivity fields from hydraulic-and tracer-tomographic data. In this paper, we applied these techniques to field experiments and to the estimation of aquifer parameters with the data collected in real tomographic aquifer tests.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations